Determining the features of temperature influence on the load-bearing structure of a hopper car with a composite cladding when transporting pellets to metallurgical enterprises - Fomin, Oleksij; Lovska, Alyona; Dzhenchako, Vadym; Zhylinkov, Olexandr; Fomina, Anna; Lytvynenko, Andrii (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports the improved load-bearing structure of a hopper car for transporting pellets and hot sinter. In order to increase the strength of the load-bearing structure of a hopper car under the influence of high temperatures from the transported cargo, the use of cladding made of composite material has been proposed. This solution also contributes to a 5 % reduction in the wagon’s tare compared to the prototype car. The dynamic load on the load-bearing structure of a hopper car was determined. This study was carried out for the case where an empty wagon was moving over an irregularity between the rail joints. The calculations showed that the studied dynamics indicators did not exceed the permissible values. At the same time, the ride of a hopper car is rated as "excellent". The main indicators of the strength of the carrying structure of a hopper car were determined taking into consideration the proposed improvement. That took into account the temperature effect exerted on the load-bearing structure of a hopper car by hot sinter. It was established that the maximum equivalent stresses occur in the zone of interaction of the girder beam with the pivot beam and are about 290 MPa. At the same time, stresses in the cladding of a hopper car are about 200 MPa, which is 12 % lower than those in a regular structure. Modal analysis was carried out to determine the frequencies and shapes of the natural oscillations of the bearing structure of a hopper car with a composite cladding. The calculation results demonstrated that the first natural frequency exceeds 8 Hz. Therefore, the safety of the wagon is provided. The coefficient of fatigue resistance of the load-bearing structure of a hopper car was calculated. It was established that its value is almost twice as high as the permissible one. That is, the resistance to fatigue of the supporting structure is provided. The research reported here could contribute to ensuring the strength of the load-bearing structures of hopper cars, reducing the cost of maintenance, and increasing the efficiency of their operation.